2019
DOI: 10.1007/s12402-018-0267-8
|View full text |Cite
|
Sign up to set email alerts
|

Parent–clinician agreement in rating the presence and severity of attention-deficit/hyperactivity disorder symptoms

Abstract: We determined the validity of a parent-report questionnaire as a research tool for rating attention-deficit/hyperactivity disorder (ADHD) symptoms in children. Using Cohen's kappa and Pearson correlation, we examined the agreement between parent reports of ADHD symptoms (using the Swanson, Nolan and Pelham Questionnaire-IV; SNAP-IV) and clinical judgment (using a semi-structured parent interview). Also, we explored factors that may be associated with the level of agreement, using regression analyses. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The much higher percentage of possible ADHD children detected by Conners score in our study (57.14% scored above 70) may be due to the high sensitivity of CPRS-R in detecting ADHD but its relative poor specificity [29,32,33]. Clinician-based rating of ADHD symptoms based on a semi-structured parent interview was found to have superior sensitivity compared to parentfilled out CPRS-R questionnaires [29].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The much higher percentage of possible ADHD children detected by Conners score in our study (57.14% scored above 70) may be due to the high sensitivity of CPRS-R in detecting ADHD but its relative poor specificity [29,32,33]. Clinician-based rating of ADHD symptoms based on a semi-structured parent interview was found to have superior sensitivity compared to parentfilled out CPRS-R questionnaires [29].…”
Section: Discussionmentioning
confidence: 49%
“…Therefore, our study needs to further evaluate these children and adolescents by a second informant, for example a teacher. Several studies (from Egypt and worldwide) have shown that parents report ADHD symptoms more frequently than teachers [19,20,[23][24][25][26][27][28][29] and that parents may not have age-appropriate behavioral expectations for their children causing overdiagnosis of ADHD. Parents were found to be more reliable in ratings of forgetfulness, whereas teachers were found to be more reliable reporters of deficits in sustained attention (teachers can quickly compare students and detect those poorly performing in a class task) [23,30].…”
Section: Discussionmentioning
confidence: 99%
“…SNAP-IV is a well-known parent-based questionnaire, which is frequently used as a primary outcome measure in intervention studies (Filho et al, 2005;Nobel, Brunnekreef, Schachar, van den Hoofdakker, & Hoekstra, 2019). In this study, it indicated that the inattention rating of ADHD participants significantly improved based on the parent and teacher SNAP-IV after PE supplementation (Table 2).…”
Section: Neuropsychological Functionmentioning
confidence: 51%
“…The SNAP‐IV 18‐item scale is an abbreviated version of the SNAP Questionnaire (Swanson, 1992) which is frequently used as primary outcome measure in treatment studies (Nobel et al, 2019). Data were collected using the Persian version of SNAP‐IV Teacher and Parent 18‐Item Rating Scale.…”
Section: Methodsmentioning
confidence: 99%